Physiological Adaptation to Left Ventricular Enlargement: Adaptasi Fisiologis terhadap Pembesaran Ventrikel Kiri - Hasan, Mahfoudh Falih; Khalaf, Fias Hadi; Mutashar, Mohammed Kadhim; Mahdi, Weam Saleh; Atiyah, Maher Abdulameer (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Physiological adaptations, especially in sports exercise, usually occur through stress on the body. The changes that occur in the functions of the body's systems are what cause development in the responses of its organs and muscles, which leads to improved athletic performance. Adaptations in response to training include: decreased the heart rate, increased the stroke volume, increased the oxygen uptake, increased the blood hemoglobin levels, and the muscle hypertrophy. Objective of the study: To evaluate the rates of the left ventricular enlargement after years of aerobic training. The research sample: includes (24) athletes and all them practice aerobic activities at the present time, as follows: Six they have (1-2) years of training. Six they have (2-4) years of training. Six they have (4-6) years of training. Six they have (6-8) years of training. The left ventricular mass was examined and diagnosed using the Echocardiogram. Data analyses: The data was analyzed using the SPSS program V. 26. Conclusions: 1-Left ventricular hypertrophy increases with the increase in the years of the aerobic training. 2-During the four years of training, left ventricular enlargement remains within the normal range. 3-after four years, Left ventricular hypertrophy begins to rise above the normal range. 3- The left ventricular hypertrophy in an aerobic athlete is not considered a pathological condition. Highlights: Adaptation: Aerobic training increases left ventricular hypertrophy over time. Timeline: Enlargement stays normal for 4 years, increases beyond normal after. Conclusion: Hypertrophy in athletes is non-pathological and a physiological adaptation. Keywords: Physiological Adaptation; Ventricular Enlargement, Athletic Heart Syndrome.